Overcoming Aggressive Behavior of Bullies Through Gestalt Counseling Approach Empty Chair Technique for Students of Islamic Boarding Schools - Nilas Siti Wulandari; Netrawati; Zadrian Ardi (Quality : Journal Of Education, Arabic And Islamic Studies, 2024)
This research aims to review and analyze literature regarding the influence of the Gestalt counseling approach using the empty chair technique in overcoming the aggressive behavior of bullies among boarding school children.  The research method used is literature study by collecting data from various sources, such as journals, books and relevant scientific articles.  The research results show that the empty chair Gestalt counseling approach has the potential to help boarding school children who experience aggressive behavior due to bullying.  This technique helps them to understand their emotions and needs and develop the ability to empathize and communicate with others.